Coil baking process modeling with neural network - Laosiritaworn,W.S. (2015)
Coil baking process is one of the critical processes in a case study company which is a manufacturer of hard disk drive actuator in Thailand. At the moment, the company is dealing with quality issue arisen from the distortion of the baked coil. Parameters affect the baking process are for example baking temperature, baking time, air ventilation pressure and position in the oven. Neural network technique was used to model the relationship between the mentioned factors and the distortion of the coil. The trained network can be used to predict coil distortion before the production occurs. Therefore, helps to reduce the defect rate. © 2012 IEEE.